The Analysis of the Influence Factor of Capital, Fishing Gear, Time of Seafaring, and Weather of Income Fisherman in Tanjung Sembilang, Samboja Subdistrict, Kutai Kartanegara Regency. - Nunuk Kasmawati; Gusti Haqiqiansyah; Said Abdusysyahid (2339-1324, 2022)
Fishermen's income is uncertain and depends heavily on the catch obtained at the time of production of the catch.The research was conducted for analyze of the influence factor of capital, fishing gear, time of seafaring, and weather of income fisherman in Tanjung Sembilang, Samboja Subdistrict, Kutai Kartanegara Regency. Kind of research data used i.e. quantitative data with primary data source by interview using questionnaires. Variable independent of research is fishing gear (X1), capital (X2), time of seafaring (X3), and weather (X4), variable dependent is income fisherman (Y). Method of analysis using analysis multiple regression, test of hypotesis, determination, and test of classic assume by using SPSS 16.0 for windows programe. The result simultaneously indicates that factor of fishing gear, capital, time of seafaring, and weather significant depends of income fisherman. Partially indicates that factor time of seafaring (1.354) and weather (-0.743) not significant depends of income fisherman, but factor of fishing gear (4.239) and factor of capital (2.518) has a significant depends of income fisherman. The highest dependent significant of income fisherman in Tanjung Sembilang, Samboja Subdistrict, Kutai Kartanegara Regency i.e. factor of fishing gear with a test-t value of 4.239 > 2.014.